Deubiquitinase PSMD14 enhances hepatocellular carcinoma growth and metastasis by stabilizing GRB2. (28th January 2020) - Lv, Jie; Zhang, Sheng; Wu, Huita; Lu, Jing; Lu, Yuyan; Wang, Fuqiang; Zhao, Wenxiu; Zhan, Ping; Lu, Junjiang; Fang, Qinliang; Xie, Chengrong; Yin, Zhenyu
Abstract: Hepatocellular carcinoma (HCC) has emerged as one of the most common malignancies worldwide. It is associated with a high mortality rate, as evident from its increasing incidence and extremely poor prognosis. The deubiquitinating enzyme 26S proteasome non-ATPase regulatory subunit 14 (PSMD14) has been reported to act as an oncogene in several human cancers. The present study aimed to reveal the functional significance of PSMD14 in HCC progression and the underlying mechanisms. We found that PSMD14 was significantly upregulated in HCC tissues. Overexpression of PSMD14 correlated with vascular invasion, tumor number, tumor recurrence, and poor tumor-free and overall survival of patients with HCC. Knockdown and overexpression experiments demonstrated that PSMD14 promoted proliferation, migration, and invasion in HCC cells in vitro, and facilitated tumor growth and metastasis in vivo . Mechanistically, we identified PSMD14 as a novel post-translational regulator of GRB2. PSMD14 inhibits degradation of GRB2 via deubiquitinating this oncoprotein in HCC cells. Furthermore, pharmacological inhibition of PSMD14 with O-phenanthroline (OPA) suppressed the malignant behavior of HCC cells in vitro and in vivo . In conclusion, our findings suggest that PSMD14 could serve as a novel promising therapeutic candidate for HCC. Highlights: PSMD14 is significantly upregulated in HCC and indicates poor tumor-free and overall survival. PSMD14 facilitates tumor growth and metastasis in vivo and in vitro . PSMD14 is a novel post-translational regulator of GRB2, inhibiting the degradation of GRB2. PSMD14 expression positively correlates with GRB2 expression in GC.